PENERAPAN PIJAT EFFLEURAGE DENGAN TOPIKAL MINYAK KELAPA MURNI PADA EKSTREMITAS TERHADAP PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI - Diah Setiani; Cantika Laksmi Bunga (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2023)
An increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements five minutes apart in a state of rest or calm is called hypertension. According to the World Health Organization (WHO), in 2015, 22% of the world's population suffered from hypertension; in Southeast Asia, the subject reach 36%. The purpose of this study is to determine the effect of apllied effleurage massage therapy with virgin coconut oil’s topical on the extremities, in order to reduce the blood pressure in hypertensive subject. This study used Quasy Experiment Design with pre-test-post test with control group approach from 22 people as samples. The results of hypothesis testing of the treatment group with paired t-test on systolic and diastolic obtained p-values of 0.000 and 0.001. Whereas in the control group, the systolic and diastolic p-values ​​were 0.053 and 0.082. Meanwhile, the results of the independent t-test statistical analysis on systolic and diastolic blood pressure in the treatment group and the control group obtained p values ​​of 0.000 and 0.010 (p <0.05), which means that there was a significant difference between the treatment group and the control group. Applying effleurage massage with virgin coconut oil’s topical on the extremities is suggested to reduce blood pressure in hypertensive subject.